Force, impulse and energy during falling with and without knee protection: an in-vitro study - Schwarze, Michael (Sci Rep, 2019)
The mechanics of protective knee padding mitigating injury from a high-force fall have not been investigated in real-life scenarios to date. This study compares the effect of wearing knee pads to unprotected impact on a hard surface. We hypothesized that knee pads reduce the force and energy transmitted to the bony structures of the knee cap compared with unprotected conditions. Eight human knee cadaver specimens were embedded and fixed with a flexion angle of 100 degrees in a custom-made drop testing device (75 kg including the knee). The usage of a knee pad led to an average peak force attenuation on impact of 15% (no pad: 5932 N SD: 2472 N; pad: 4210 N SD: 2199 N; p < 0.001). Contact time on the plate was higher with a knee pad (no pad: 0.015 s SD: 0.009 s; pad: 0.028 s SD: 0.014 s; p < 0.001). Therefore, the observed impulse was also increased (no pad: 62.2 Ns SD: 17.8 Ns; pad: 74.6 Ns SD: 18.6 Ns; p < 0.001). This effect diminished as drop height was increased. Energy dissipation, defined as the difference between kinetic energy pre-impact and peak potential energy post-impact, was higher without a knee pad (no pad: 10.5 J SD: 6.2 J; pad: 4.2 J SD: 5.0 J; p < 0.001). The results from this study illustrate the magnitude of influence that knee pads have on peak forces, transmitted impulse, and energy transfer from a high-force impact in real-life scenarios. Contrary to expectations, the knee pad did not act as a mechanical damper. The mechanical behavior more closely resembled a spring that temporarily stores energy and consequentially reduces peak forces upon impact. Based on this study, future developments in padding might benefit from focusing on the aspect of energy storage and temporarily delayed energy dissipation.